Enhancing Science Concept Mastery through a Structured Inquiry Learning Model Integrated with Electronic Teaching Materials - Fitria Wahyu Wulansari; Riva Ismawati (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Mastery of science concepts among eighth-grade students at SMPN 4 Magelang remains relatively low, as indicated by limited engagement in learning activities and assessment results below expected competency standards. This issue requires pedagogical intervention. This study aimed to enhance science concept mastery through a structured inquiry learning model integrated with electronic teaching materials. Collaborative classroom action research was conducted over three cycles with 32 students participating for six weeks. Concept-mastery tests based on Bloom’s revised taxonomy were used as instruments, and data were analyzed using mean scores, achievement rates, and N-gain. Findings showed consistent improvement from Cycle I to Cycle III, with posttest scores increasing from 68 to 81, N-gain values rising from .44 to .69, and completion rates improving from 44% to 81%. The structured inquiry model facilitated students’ conceptual understanding through systematic scientific procedures, while electronic teaching materials enhanced visualization and interactivity. These results demonstrate the effectiveness of combining structured inquiry with digital learning resources to strengthen students’ comprehension and application of scientific concepts